The daily relations of co-rumination and perseverative cognition - Lilla Nóra Kovács; Natália Kocsel; Zsófia Tóth; Tamás Smahajcsik-Szabó; Szilvia Karsai; Gyöngyi Kökönyei (Scientific Reports)
Abstract Emotion regulation plays a crucial role in responding to daily stressors. While intrapersonal emotion regulation has received significant attention, the role of interpersonal emotion regulation remains understudied. This study aimed to explore the associations between intrapersonal perseverative cognition (i.e., rumination and worry) and interpersonal perseverative cognition (i.e., co-rumination), in the context of daily negative events. A daily diary study was conducted with a sample of university students (N = 178). The study comprised a baseline survey assessing trait-level variables, followed by a diary study where participants were sent an approximately two-minute-long survey every evening for 10 consecutive days. The findings indicated that daily co-rumination was associated with daily intrapersonal perseverative cognition, even when controlling for trait-level worry. The association between intra- and interpersonal perseverative cognition was stronger in the presence of daily negative events. Our findings indicate a need for further investigation into the contemporaneous relationship between co-rumination and intrapersonal rumination/worry, to ascertain their unique or joint adverse effects on mental health, especially within the context of daily negative events.